2010
DOI: 10.1615/critreveukargeneexpr.v20.i3.40
|View full text |Cite
|
Sign up to set email alerts
|

Role of Parathyroid Hormone (PTH) and PTH-related Protein (PTHrP) in Regulating Mineral Homeostasis during Fetal Development

Abstract: Parathyroid hormone (PTH) and PTH-related protein (PTHrP) play complementary and overlapping roles in regulating fetal mineral homeostasis. PTHrP is expressed within the growth plate, directs endochondral bone formation, and determines the fate of chondrocytes before bone formation can be initiated. It is expressed in placenta and is present at high levels in the fetal circulation. It stimulates placental calcium (and possibly magnesium) transfer and raises blood mineral levels above ambient maternal values in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Thus, the PTHrP gene may have similar roles in the paracine or autocrine regulation of local Ca homeostasis. A previous study reported that PTHrP was expressed in the placenta and was present at high levels in the fetal circulation, supporting that PTHrP stimulates placental calcium transfer (Simmonds and Kovacs, 2010). The PTHrP gene was moderately expressed in the water buffalo placenta in this study, indicating that PTHrP in water buffalo may play a role in placental calcium transfer.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, the PTHrP gene may have similar roles in the paracine or autocrine regulation of local Ca homeostasis. A previous study reported that PTHrP was expressed in the placenta and was present at high levels in the fetal circulation, supporting that PTHrP stimulates placental calcium transfer (Simmonds and Kovacs, 2010). The PTHrP gene was moderately expressed in the water buffalo placenta in this study, indicating that PTHrP in water buffalo may play a role in placental calcium transfer.…”
Section: Discussionsupporting
confidence: 84%
“…Studies in genetically manipulated mice confirm that PTHrP controls placental calcium transport to bring about mineralization of the fetal skeleton (50), with the main PTHrP source being the placenta.…”
Section: Placental Calcium Transportmentioning
confidence: 99%
“…50,53,54 Absence of either fetal parathyroids, PTH, or PTHrP lead to a similar degree of hyperphosphatemia. 50,53,54,74,75 Overall, these data indicate that PTHrP and PTH both regulate fetal mineral homeostasis.…”
Section: Minerals and Calciotropic Hormonesmentioning
confidence: 68%
“…PTH may also play a role in stimulating placental calcium transport through its local expression in the placenta, as observed in recent work (Figure 63.2). 50, 74 The factors that stimulate placental phosphorus transport are unknown; PTHrP and PTH had no effect when administered to fetal lambs. 77,78 …”
Section: Placental Mineral Transportmentioning
confidence: 99%